GEOGRAPHICAL INFORMATION SYSTEMS IN ARCHAEOLOGICAL CARTOGRAPHY OF SOUTH KAZAKHSTAN - Baitanayev B.А.,; Antonov M.A.,; Yergeshbayev A.A.,; Shayakhmetov A.Kh., (Scientific Journal of Pedagogy and Economics, 2020)
The article presents available data on mapping based on archaeological exploration with the subsequent involvement of modern GIS technologies. Before the start of work on the compilation of archaeological maps, there was made an analysis of the history of the appearance of similar documents. Research data were taken from both domestic and neighboring countries. It should be noted that current technologies allow you to create maps with accurate data and with detailed reference to the terrain, while using all the available data: these are high-quality space images, radar and GPS data, orthophotomaps with altitude maps. This in turn will give a more detailed understanding of the functioning of the Karaultobe-type monuments being studied. To compile an archaeological map, a database was collected consisting of information about Karaultobe and settlement monuments of the Ispijab historical and cultural district. The main data are the results of exploration and surveys of monuments such as Karaultobe. The analysis was based on experimental methods in GIS. The basis of the maps is radar and GPS data. For analysis, the article used the capabilities of ArcGIS - a special geographic information software product. With the help of special tools, surveys of individual sites and facilities were carried out. The coordinates of each Karaultobe and the altitude map were used separately for analysis. The points themselves, this is a set of data obtained using GPS in field research, in particular because of archaeological exploration. The altitude map is highresolution radar data (30 meters) available on the US Geological Survey website. Data on the position of the Karaultobe towers, obtained using GPS, were corrected from satellite images to avoid errors. During the work, a digital map was created that can be used to display visibility data from monuments and their work in conjunction with settlement monuments in the region. Objects such as Karaultobe and towns with settlements of the region are studied during the creation of archaeological maps. The basic Karaultobe were chosen as the studied objects. These objects have a characteristic trapezoidal shape and large dimensions with a long range of visibility from them. Settlement structures are chosen based on assumptions about the interaction of towns and settlements with watchtowers. Maps are created for work that includes displaying study analyses as a database, which allows you to further supplement and correct all the information collected. The work on creating the map within the project is aimed at producing a series of maps. This series displays the main map, which displays all objects, as well as individual more detailed maps of the selected regions and maps with the results of terrain analyses. In the publication, authors do not use all maps, but individual, dimensioned options, with simplified annotations. In general, as a result of the creation of a cartographic base on the topic of research, not only maps were prepared, but also a comparative analysis of Karaultobe. Based on these, an important detail in the analysis is the compilation of a table with Karaultobe data. Several Karaultobe chains were analyzed and the boundaries of visibility between them were determined. The results of the analysis are important due to the fact that on the basis of the data obtained it is possible to reconstruct the missing ones as a result of the destruction of Karaultobe, to reproduce their former height. It is also possible to determine the way Karaultobe functions not only in terms of visual contact with settlement monuments, but also as a complex warning system.